Ferroelectric properties of Pb(Zr1/2Ti1/2)O 3-Pb(Zn1/3Nb2/3)O3 ceramics under compressive stress applied perpendicular to electric field - Muangjai Unruan (2018)
Effects of perpendicular compressive stress on the ferroelectric properties of ceramics in PZT-PZN system were investigated. The (1-χ)Pb(Zr 1/2Ti1/2)O3-χPb(Zn1/3Nb 2/3)O3 or (1-χ)PZT- (χ)PZN (χ = 0.1-0.5) ceramics were prepared by a conventional mixed-oxide method. The ferroelectric properties were measured under compressive stress applied perpendicular to an electric field direction at stress levels up to 90 MPa using a compressometer in conjunction with a modified Sawyer-Tower circuit. It was found that with increasing compressive stress the area of the ferroelectric hysteresis (P-E) loops, the maximum polarization (Pmax), and the remanent polarization (Pr) decreased, while the coercive field (Ec) remained relatively constant. These results were interpreted through the domain switching, clamping of domain walls and de-poling mechanisms. © (2010) Trans Tech Publications.